Smallpox: leaving its mark on public health - Moore, Corey B. (International Journal Of Community Medicine And Public Health, 2019)
Smallpox was one of the most lethal human pathogens in history. It originated around 10,000 years before common era (BCE) in North-eastern Africa, and spread world-wide through human migration and increasing population densities with periodic epidemics throughout the world. By the middle of the 18th century, around one million Europeans each year were contracting the disease with approximately one third of adults and 90 percent of infants succumbing to it. The mortality rate in the immune-naïve populations of the Aztecs and the Incas were as high as 90%. Survivors were left with disfiguring scars and one third were blinded. After the bubonic plague, it was the most feared disease. It affected the outcome of many wars, conquests and the development of many civilisations.